In vitro Culture of Human Testicular Stem Cells on Feeder-Free Condition - Z Piravar; M Jeddi-Tehrani; MR Sadeghi; A Mohazab; A Eidi; MM Akhondi (JRI, 2013)
Background: Spermatogonial stem cells are subpopulation of spermatogonial cells in testis tissue that support beginning and maintenance of spermatogenesis. Ubiquitin carboxy-terminal hydrolase L1 (UCHL1) could be a specific marker for identification of spermatogonial stem cells including spermatogonial sperm cells (SSCs) in testis tissue and during the culture; therefore we undertook this study to culture these human testicular stem cells (hTSCs) in vitro and approved the presence of human testicular stem cells (hTSCs) by UCHL1, also known as PGP9.5. Methods: Enzymatic digestion of human testicular biopsies was done by collagenase IV (4 mg/ml) and trypsin (0.25%). Differential plating of testicular cells in DMEM/F12 and 10% FBS was applied for 16 hr. Floating cells were collected and transferred onto laminin-coated plates with Stem-Pro 34 media supplemented with growth factors of GDNF, bFGF, EGF and LIF to support self-renewal divisions; testicular stem cell clusters were passaged every 14 days for two months. Spermatogonial cells propagation was studied through Expression of UCHL1 in testis tissue and the entire testicular stem cell culture. Results: Testicular stem cell clusters from 10 patients with obstructive azoospermia were cultured on laminin-coated plates and subsequently propagated for two months. The average of harvested viable cells was approximately 89.6%. UCHL1 was expressed as specific marker in testicular stem cells entire the culture. Conclusion: Human testicular stem cells could be obtained from human testicular tissue by a simple digestion, culturing and propagation method for long-term in vitro conditions. Propagation of these cells approved by specific marker UCHL1, during the culture period.
Keywords: Human testicular stem cells, Laminin, Long term culture, UCHL1